Family Farming in Colombia : Multifunctionality-based Case Studies and its Contribution to Peace (2016)
Family farming in Colombia is represented by peasants, indigenous people, Afro-descendants, fishermen, urban and neo-rural farmers who live, generally, in conditions of poverty and neglect. It is subordinated by national rural policies and programs and there are no differential policycriteria that recognize its particularities and strengthen its capacities; however, it is responsible for the production of much of the staple food for Colombians and has a strong representation in the national economy. Based on the analysis of several case studies in the country, this studyproposes the recognition of the family farming category as a strategy that supports its forms of production and integrates them without deconstructing its particular rationality. Granting multiple functions to farm systems represents a sociocultural strategy for farming families to adapt to external situations that threaten their continuity; additionally, family farmers maintain an ongoing struggle to assert their autonomy and rights as a declaration of socio-political resistance. The need for differentiated policies on family farming that are comprehensive, systematic and long term, and that allow farmers to have access to land, is highlighted. Finally, a reordering is proposed to make viable an inclusive national agricultural modernization, not only for economies of scale, but economies of diversification, food sovereignty, local democracy, solidarity economy and sustainability as possible alternatives for a new rural development model that contributes to the desired peace for the country.